Emergence of Agile Methods: Perceptions from software practitioners in Malaysia - Asnawi, Ani Liza; Gravell, Andrew M.; Wills, Gary B. (2012)
Agile methods are an established process for developing software nowadays. There is, however, less evidence on their usage among software practitioners in Malaysia. While the methods have become mainstream in other regions, that is not the case in this country. This paper empirically investigates the perceptions of Agile methods usage from seven organisations involving 14 software practitioners in Malaysia. Our participants are using Scrum and have a maximum of five years experience. We categorised our findings in terms of awareness, introduction, and challenges they are facing, together with the suggested and practiced solution from them. Interestingly, a change in mind set when practicing Agile was identified to be helpful in reducing the challenges. Lastly we present the practices in Agile they perceived to deliver the most benefits. We found that the use of Agile is still emerging in the country, and awareness is still lacking especially within the government sector. Although several challenges have been encountered when introducing Agile in their organisations, the benefits of Agile are reported to be in Agile practices such as: the involvement from all parties from the beginning, daily stand-up meeting, iterative and incremental, applying burn down chart, sprint and continuous integration. We aim to provide awareness and knowledge about Agile methods to the practitioners in the country and the nearby region. This paper can serve as a reference to the early adopters who intend to use Agile methods in the future.